The role of literacy in the association between educational attainment and depressive symptoms - Thu T. Nguyen; Eric J. Tchetgen Tchetgen; Ichiro Kawachi; Stephen E. Gilman; Stefan Walter; M. Maria Glymour (SSM: Population Health, 2017)
There is a consistent association between education and depressive symptoms, but research on the mechanisms to explain this association remains limited. No study has formally evaluated the extent to which the association between education and depressive symptoms is mediated through a foundational skill such as literacy. Inverse odds ratio weighting (IORW) was used to estimate total, natural direct, and natural indirect effects in examining literacy as a mediator of the association between education and depressive symptoms. Health and Retirement Study participants born in the U.S. between 1900 and 1947 were interviewed biennially for up to 12 years (N = 16,718). Literacy was assessed with a brief vocabulary measure. Depressive symptoms were measured using the 8-item Centers for Epidemiologic Studies-Depression (CES-D) scale. Decomposition estimates were derived using regression analyses of repeated measures of depressive symptoms. Standard errors were obtained using a nonparametric bootstrap with the individual as the independent unit to account for dependence of observations within an individual. In a large cohort of older Americans, a one standard deviation difference in educational attainment (~ 3 years) was associated with a 0.35-point decrement in CES-D score (95% CI: -0.38, -0.32). This decrement represents a 0.22 standard deviation difference in depressive symptoms. Using IORW, the estimated effect of education on depressive symptoms mediated through literacy was -0.10 (95% CI: -0.18, -0.01), which represents 28% of the total effect. Education confers many benefits; as demonstrated by this study for depressive symptoms, one important benefit is literacy.